Effects of jasmonic acid in reducing cucumber mosaic virus infection and improving growth performance of chili (Capsicum annuum L.) - Johari @ Shaari, Nur Asna Faiqah (2018)
The high demand for chili has made agriculture entirely dependent on application of chemical pesticide to control pests and diseases. Results demonstrated that plants treated with pesticide significantly affected the number of pests such as aphids, thrips and mites which reduced the percentage of disease incidence up to 80%. However, regarding the long-term effect of pesticide toxicity, many researchers have developed alternative approaches which could improve plant productivity and give benefits to human and environmental health. In this study, jasmonic acid (JA), a potential plant elicitor had been tested using different concentrations (0.6 mM and 1.0 mM) and spray frequencies (single, double and triple application) to evaluate the efficacy in promoting growth performances, physiological responses, improving yield and reducing disease incidence. Results demonstrated treatment of 0.6 mM JA with double spray showed the outstanding positive effect compared to others in lowering the disease incidence by 50%. Despite of insignificant in concentration and spray frequencies factors, concentration of JA at 0.6 mM with double spray succeeded in improving high fruit yield which produced similar results to plants treated with concentration 1.0 mM of JA in double and triple sprays. Therefore, the next study to evaluate the effect of JA on chili plant infected with Cucumber Mosaic Virus (CMV) was carried out using concentration of 0.6 mM with double spray. CMV was reported to be one of the most prevalent cucumovirus in Malaysia due to its large host range and insect vectors. The findings revealed that CMVinfected plant treated with JA had the highest inhibitory effect on CMV infection at 30 days post inoculation (dpi) compared to untreated and pesticide-treated plants that were severely damaged. Due to low percentage of disease severity in JA application, the chili yield increased up to 95% and significantly raised the dry matter accumulation in leaves, stems and roots. The elicitation of JA had a significant impact on activities of catalase (CAT), ascorbate peroxidase (APX), guaiacol peroxidase (GPX), ascorbic acid (AsA), a-tocopherol and carotenoids (CAR) in leaves and fruits. In the JA-treated plants a significant increase in AsA, CAT, APX and GPX activities showed that these antioxidants were essential to detoxify reactive oxygen species (ROS) at 14 dpi (flowering stage) while AsA and ɑ-tocopherol was suggested to become the selective protection against CMV infection at 30 dpi (fruiting stage). Among the enzymatic antioxidants, GPX had the highest activity in chili fruit of JA-treated plants followed by CAT and APX. These results suggested that exogenous application of JA could effectively reduce CMV infection by enhancing activities of enzymatic antioxidants and concentration of non-antioxidant to quench excessive ROS. So, it can be concluded that the optimum concentration and spray frequencies of JA can become a promising tool for reducing CMV disease thus improving the growth performances in chili plants as an alternative method to replace or reduce the pesticide use.